2022
DOI: 10.21037/atm-21-4595
|View full text |Cite
|
Sign up to set email alerts
|

Factorial design and post-antibiotic sub-MIC effects of linezolid combined with fosfomycin against vancomycin-resistant enterococci

Abstract: Background: Antimicrobial drug resistance, including vancomycin-resistant enterococci (VRE), has long been an inescapable clinical problem. If vancomycin loose its therapeutic relevance, a regimen of linezolid combined with fosfomycin may provide an alternative option.Methods: In this study, the in vitro antimicrobial effect of linezolid combined with fosfomycin on several different types of VRE was investigated using a checkerboard method and time-kill assays. Based on the results of the 24 h time-kill assays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…A combination of antibiotics can effectively reduce the dose of the two antibiotics, which in turn can achieve the purpose of bacteriostasis at a lower concentration ( Algharib et al., 2020b ; Hussein et al., 2022 ; Yan et al., 2022 ). Our study successfully achieved the goal of improving antibiotic susceptibility by inhibiting biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A combination of antibiotics can effectively reduce the dose of the two antibiotics, which in turn can achieve the purpose of bacteriostasis at a lower concentration ( Algharib et al., 2020b ; Hussein et al., 2022 ; Yan et al., 2022 ). Our study successfully achieved the goal of improving antibiotic susceptibility by inhibiting biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…Broth Micro-Checkerboard was used for isookanin and five β-lactam antibiotics combination as previously reported with slight modifications ( Rogers et al., 2010 ; Yan et al., 2022 ). Briefly, 50 μL of ploidy dilution antibiotics working solution add it to columns 2-12 of the 96-well plate, and 50 μL of ploidy dilution isookanin solution added it to row A-G of the plate.…”
Section: Methodsmentioning
confidence: 99%
“…First, in vitro assay data showed that linezolid combined with fosfomycin had a highly synergistic effect, of which the linezolid group showed similar bacteriostatic effects, causing a ~1 log 10 decrease in the three clinical strains after 24 h compared to the initial concentration at 0 h. However, Yan et al showed a trend of gradual drug resistance when a sub-inhibitory concentration of 1 mg/L linezolid was used in the treatment of VRE. 11 According to a survey of 1442 clinically collected Enterococcus isolates in the Czech Republic from 2009 to 2019, linezolid-resistant Enterococcus faecalis (LREF) increased from 0 in 2009 to 36 in 2019. 33 Subsequently, a global statistical analysis showed that of 69,291 Enterococcus isolates, 1646 were LREF isolates, indicating a prevalence rate of 2.2%.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, linezolid combined with fosfomycin exhibited a good synergistic effect and exerted a sustained bactericidal effect. Yan et al further suggested that linezolid combined with fosfomycin could prolong the post-antibiotic effect, 11 which was beneficial for prolonging the treatment time. Jiang et al speculated that the combination of drugs might be a beneficial result of the synergistic closure of their respective mutation selection windows (MSW).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation